Introduction to naval architecture - Tupper, E. C. (Amsterdam ; Boston : Elsevier, Butterworth Heinemann, 2004)
The fundamental characteristics of a ships design, and how they affect its behaviour at sea are of crucial importance to many people involved in the design, construction, operation, and maintenance of all marine vessels. Naval architects and those working in ship design need to understand these principles in depth. Marine engineers must likewise recognise the degree to which their activities are influenced and bounded by these principles. Finally, senior crew both Ships Engineers and Commanders need an understanding of the principles of naval architecture in order to properly fulfil their duties. This book offers a clear and concise introduction to the subject and is of great value to both students and practising professionals in all of the above fields. *Covers introductory level courses in Naval Architecture and Marine Engineering *Updated to cover key developments including double-hulled tankers *Fully revised fourth edition accompanied by exercises and worked solutions for the first time.
Introduction -- Ship design -- Definition and regulation -- Ship form calculations -- Flotation and initial stability -- The external environment -- Stability at large angles -- Launching, docking and grounding -- Resistance -- Propulsion -- Ship dynamics -- Seakeeping -- Manoeuvring -- Main hull strength -- Structural elements -- The internal environment -- Ship types -- Appendix A. : Units, notation and sources -- Appendix B. : The displacement sheet and hydrostatics -- Appendix C. : Glossary of terms -- Appendix D. : The Froude notation -- Appendix E. : Questions.
"Formerly Muckle's Naval architecture for marine engineers"--Cover.
Includes bibliographical references and index.
Keywords: Naval architecture; Electronic books